O conceito de tolerância e seu valor pedagógico: questões sobre a pluralidade e a coexistência pacífica - Rodrigues, Marcus Rafael (2016)
The research now engendered has as a key objective to contribute to overcome the supposed obsolescence that was associated prematurely with the term “tolerance”, especially today. It performs a brief historical contextualization, as well as a biographical matrix, while considering authors who notably contribute to the semantic exploration of how tolerance has become synonymous with asymmetry, even though originally focused on mutual and equal consideration of human coexistence. This paper still investigates some philosophical aspects that underlie the understanding of the tolerant way of acting, based on its integration with rationality, elaborated bearing in mind ideas by Rouanet. Ideologies are presented as detractors of the tolerant way of acting when considering human relationships from the subject-object binomial, focusing on hierarchy. The communicative action of Habermas and Jasper’s Comprehensive present themselves as an alternative to the said binomial perspective. Weighted by Marcuse and Arendt, the limits and purposes of tolerating demonstrate the political importance of the discussion on the subject. Finally, it is intended to overcome the preconceptualization of this subject, since this is a naïve attitude, belonging to the ideological view aimed at domination. To achieve this, we used the initiatives taken up tolerance as a concept to be taught and therefore pedagogically located in school education. This was made possible by the philosophical foundations provided by Walzer and Freire, and also the intellectual efforts of practical proposals to teach to tolerate.